Ruang Bangsa dan Ruang Alternatif dalam Novel “Lingkar Tanah Lingkar Air” Karya Ahmad Tohari - Ricky Yudhistira Nasution; Arie Azhari Nasution; Evi Marlina Harahap (Balai Bahasa Provinsi Bali, 2022)
This research aims to discover the nation space construction and the alternative space that Ahmad Tohari offers in the novel “Lingkar Tanah Lingkar Air”. Theory used in this research is the politics of postcolonial space by Sara Upstone (2009), particularly at the level of nation space which has basic structure of space, place, overwriting, (b)order, chaos and post-space. The theory and problem selection in this research are related to the phenomenon of the re-emergence of separatist groups in Indonesia. In this research, the method used is qualitative descriptive. The result of the research indicates that the construction of nation space in LTLA novel have the form of Republic with a presidential system of government in which there are place and (b)order that still inherit the colonial space construction. The nation space of Indonesia demand for homogeneity, stability, constancy and fixed, consequently bring up the groups that against the State. Meanwhile, the alternative space offered by Ahmad Tohari is